Humanin protects cortical neurons from calyculin A-induced neurotoxicities by increasing PP2A activity and SOD. (3rd June 2021) - Zhao, Jinfeng; Zeng, Yu; Wang, Yaxin; Shi, Junzhen; Zhao, Wenhui; Wu, Baoai; Du, Huizhi
Abstract: Background: Humanin (HN) is an extensive neuroprotective peptide. This study aims to investigate the neuroprotective effects of HN on Calyculin A (CA)-induced neurotoxicities in cortical neurons and the underlying mechanism. Methods: CA was added into the cultured cortical neurons to induce neurotoxicity. Cortical neurons were preincubated with HN which plays a protective role. 3-(4, 5-Dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT), lactate dehydrogenase (LDH), and Calcein-AM were applied to evaluate the neural insults. Caspase 3 signal and Tunnel were performed to test neural apoptosis. Western blot analysis was used to detect the expressions of phosphorylated tau. The corresponding kits were used to measure the contents of malondialdehyde (MDA) and superoxide dismutase (SOD), and the activity of PP2A, respectively. Results: HN preincubation preserved cell viability, protected the neurons, alleviated oxidative stress, and reserved PP2A activity. It also blocked tau overphosphorylation at Ser199/202, Ser396, and Thr231 sites and protected neurons against CA-induced insults. Conclusion: These results suggest that HN may serve as a potential therapeutic agent to prevent the pathological changes induced by CA via modulating the activity of PP2A and oxidative stress in neurodegenerative diseases.